Relationship between supervisor's role and job perfomance :does motivation to learn act as a mediating role? - Sheela Chitra, A/P Chandra Segaran. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study was conducted to examine the mediating role of motivation to learn in the relationship between supervisor’s role and job performance. Data were collected through in-depth interview and survey questionnaires. For the survey method, 100 usable questionnaires were collected from technical employees who are working at the Technical Division of Dewan Bandaraya Kuching Utara, Sarawak (DBKU). The outcomes of stepwise regression analysis showed that the inclusion of motivation to learn in the analysis had increased the effect of supervisor’s role (i.e., support and communication) on job performance. This result demonstrates that motivation to learn does acts as a full mediating role in training management model of the organization. In addition, implications of this study to training management theory and practice, methodological and conceptual limitations, as well as directions for future research are elaborated.